Gummy Smiles: Etiologies, Diagnoses & Formulating A Clinically Effective Treatment Protocol - Sami Mohammed Saeed Alamri; Faisal Saeed Salem Alshahrani; Ibrahim Mohammed Abdulrahman Alshehri; Mohammed Abdulaziz Ali Alobaydaa; Wafaa Aiyd Abdallah Alhazri; Suad Awadh Melfi Alanazi; Sultan Mohammed Oudh Alganame; Rayan Mohmoud Mohammed Eskandrani (International Journal of Medical Toxicology and Legal Medicine, 2024)
The smile is the most accepted facial emotion that enhances a case’s self-esteem, social skills, and capacity for interpersonal interaction. Excessive gingival exposure, commonly referred to as a gummy smile is a non-aesthetic disorder marked by an overexposure of the gingiva when smile. The demand from cases to address elevated smile lines has risen in recent years. This involves gingival overexposure, referred to as gummy smile or excess gingival show. A Smile by gums is a prevalent variant, particularly between females, with an occurrence rate of 10.5 to twenty-nine percent. Cases frequently possess insufficient awareness and knowledge concerning Botox treatments for gummy smiles; therefore, the clinician must thoroughly clarify all treatment alternatives and their potential effects with the case. Previous research has proposed classifying gummy grins according to their etiopathogenic variables to identify the most advantageous treatment option. These investigations indicate that a pronounced smile may be classified as dentoalveolar, resulting from excessive sagittal or vertical growth of the jaw; dentogingival, arising from alterations in the typical trajectory of dental eruption that diminish the clinical crown; muscular, because of excessive activity of the perioral musculature; or mixed, stemming from multiple etiological factors.